2018
DOI: 10.1016/j.cbi.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The roles of breast cancer resistance protein (BCRP/ABCG2) and multidrug resistance-associated proteins (MRPs/ABCCs) in the excretion of cycloicaritin-3-O-glucoronide in UGT1A1-overexpressing HeLa cells

Abstract: Cycloicaritin is a bioactive natural phenolic compound from Epimedium species. However, the glucuronidation and excretion which would influence oral bioavailability and pharmacokinetics of cycloicaritin still remain unknown. Here we aimed to establish UGT1A1 stably transfected HeLa cells, and to determine the contributions of BCRP and MRPs transporters to excretion of cycloicaritin-3-O-glucuronide. First, β-estradiol was used to validate the expression of active UGT1A1 protein in engineered HeLa1A1 cells. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…MRP1 is primarily expressed in physiological disorders, such as the blood-brain barrier and may limit drug uptake and retention 110 . Activation of the PI3K/AKT pathway promotes via MDR by regulation of the expression of a variety of cellular processes, including apoptosis (Bax/Bcl-2) and drug transport (MRP1) 111 , where nuclear factor erythroid-derived 2 (Nrf2) is a nuclear regulator of MRP1, and it is part of the reason for MDR.…”
Section: Mrp1mentioning
confidence: 99%
“…MRP1 is primarily expressed in physiological disorders, such as the blood-brain barrier and may limit drug uptake and retention 110 . Activation of the PI3K/AKT pathway promotes via MDR by regulation of the expression of a variety of cellular processes, including apoptosis (Bax/Bcl-2) and drug transport (MRP1) 111 , where nuclear factor erythroid-derived 2 (Nrf2) is a nuclear regulator of MRP1, and it is part of the reason for MDR.…”
Section: Mrp1mentioning
confidence: 99%
“…The maximal clearance (CL max ) for Hill equation model was obtained using equation (5). [23] The CL int values for two-site kinetics were the V max /K m of low-affinity enzyme (i.e., V max2 /K m2 ). [28] V ¼…”
Section: Enzyme Kinetic Evaluationmentioning
confidence: 99%
“…This was consistent with our previous reports in which BCRP and MRP4 participated in excretion of conjugated glucuronides of several prenylated avonoids (or avanones). 21,22,25,41 Another data showed that when the function of BCRP or MRP4 transporters was inhibited, signicant down-regulation of cellular glucuronidation of bavachinin in HeLa1A1 cells was observed (Fig. 3e).…”
Section: Discussionmentioning
confidence: 93%
“…43 A remarkable limitation is the unexplained role of MRP2 in excretion of G1 due to the absence of MRP2 transporters in HeLa1A1 cells. [21][22][23]25,41,43 Furthermore, MDCKII-MRP2-UGT1A1 cells could well characterize the glucuronidation by UGT1A1 and glucuronides excretion by MRP2 transporters. 45 In addition, Mrp2 (Abcc2) knock-out mice were usually used to evaluate the roles of Mrp2 according to the pharmacokinetic behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation